Strengthening Teacher Competence and Performance through the Teacher Professional Education Program (PPG) in Improving the Quality of Learning - Rahma Septa Ramadhan; Tatia Desfika; Nabela Veronika; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
This study aims to analyze the role of the Teacher Professional Education Program (PPG) in strengthening teacher competence and performance and its impact on improving the quality of learning. This research uses a qualitative approach with a library research method. Data were obtained from various secondary sources such as scientific journals, books, and relevant educational policy documents. Data collection was carried out through documentation by reviewing and analyzing various literature related to teacher competence and the PPG program. Data analysis used content analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the PPG program plays an important role in improving teachers’ pedagogical, professional, social, and personal competencies. These competencies influence teachers’ performance in planning, implementing, and evaluating the learning process. In addition, the PPG program encourages teachers to be more innovative in utilizing technology and implementing student-centered learning strategies. Therefore, the PPG program contributes positively to improving the quality of learning in schools.